The Impact of Family Violence on Bullying Behaviour Among Secondary School Students in Ilorin Metropolis - Ilori, Oyedotun Dolapo; Akerele, Patrick O.; Michael, Ifeoluwa Blessing (Buletin Konseling Inovatif, 2025)
Family violence remains a significant social issue with far-reaching consequences for adolescents, particularly in shaping their behavioural tendencies, including bullying. This study examines the impact of family violence on bullying behaviour among secondary school students in Ilorin Metropolis, which comprises three Local Government Areas (Ilorin South, Ilorin West, and Ilorin East). The study adopts a descriptive survey research design to assess the extent to which exposure to family violence influences students' bullying behaviours, while also considering the role of peer influence. A multi-stage sampling technique was employed to select 417 students from both public and private secondary schools in Ilorin Metropolis. A structured questionnaire, divided into four sections (demographics, family violence, peer influence, and bullying behaviour), was used for data collection. The instrument was validated by experts and tested for reliability through a pilot study, yielding a Cronbach’s Alpha coefficient of 0.89. Data analysis was conducted using descriptive statistics (mean, frequency, percentages) and inferential statistics (Pearson’s correlation, regression analysis, t-tests, and ANOVA). The findings of the study revealed that family violence and peer influence significantly contribute to bullying behaviour among secondary school students. The majority of adolescents in Ilorin Metropolis experienced moderate levels of family violence, peer influence, and bullying behaviour. Furthermore, peer influence was found to mediate the relationship between family violence and bullying. The study highlights the need for targeted interventions, including school-based counseling programs, parental education on non-violent conflict resolution, and stronger enforcement of anti-bullying policies in schools. The findings also underscore the importance of collaborative efforts among parents, educators, and policymakers to mitigate the effects of family violence and peer influence on adolescent behaviour.